Sensitive windows for within- and trans-generational plasticity of anti-predator defences - Tariel-Adam, Juliette; Luquet, Émilien; Plénet, Sandrine (Peer Community Journal)

(untitled)
Transgenerational plasticity could be an important mechanism for adaptation to variable environments in addition to within-generational plasticity. But its potential for adaptation may be restricted to specific developmental windows that are highly sensitive and responsive to environmental cues. Determining these sensitive windows is essential to understand the temporal dynamic of environmental cue detection, phenotype induction and selection. We examined the sensitive windows of both within- and trans-generational plasticity of anti-predator defences in the freshwater snail Physa acuta. Parental snails were exposed to olfactory cues of their crayfish predator at different exposure windows: embryonic development, early, mid or late post-embryonic development. Behavioural and morphological defences were then assessed in adult parents and offspring. The sensitive window of within-generational plasticity was the embryonic development, the whole post-embryonic development, or a combination of early-life and late development depending on the defence. This showed that early-life periods of development (embryonic and early post-embryonic) are sensitive windows of within-generational plasticity. However, the sensitive window also persisted until late developmental stages for some defences, providing evidence that the early-life is not the only sensitive window as empirical and theoretical studies often state. There were less sensitive windows for transgenerational plasticity: embryonic and/or mid post-embryonic development. Interestingly, the embryonic period was a sensitive window of transgenerational plasticity for a defence only when it was also a sensitive window of within-generational plasticity for that defence. On the opposite, the mid post-embryonic development was a sensitive window specific to transgenerational plasticity. This suggests that transgenerational plasticity, although linked to within-generational plasticity by the embryonic sensitive window, may also be induced via a specific channel, independent of within-generational plasticity induction and expression. Finally, the late developmental window was never a sensitive window of transgenerational plasticity as it was theoretically expected. This result may be explained by the potential long-term reliability of parental cues in our system. It is worth noting that we did not find any sensitive window for some defences, either because none of them induced the defence or all exposure windows induced the defence in a similar magnitude. Overall, the developmental window of cue exposure shapes within- and trans-generational responses and thus brings complexity to the study of phenotypic plasticity, notably when it comes to determining its adaptive potential.